Number of parity/live birth(s) and cardiovascular disease among Iranian women and men: results of over 15 years of follow-up - Seyyed Saeed Moazzeni; Hossein Toreyhi; Samaneh Asgari; Fereidoun Azizi; Fahimeh Ramezani Tehrani; Farzad Hadaegh (BMC, 2021)
Abstract Background Most previous studies conducted in non-Middle Eastern populations have suggested that an increase in the number of parity/live birth(s) leads to cardiovascular disease (CVD) development, although their findings were inconclusive on this issue for both sexes. Biologic and socioeconomic pathways were suggested to explain this association. We studied this issue among urban Iranian men and women. Methods In this population-based cohort study, which included 3929 women and 2571 men aged ≥30 years, data for the number of parity/live birth(s) were obtained by a standard questionnaire. Participants were then annually followed for CVD events. Multivariable Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the number of parity/live birth(s) and other traditional CVD risk factors. Results During more than 15 years of follow-up, 456 and 524 CVD events have occurred among women and men, respectively. Among women, a J-shaped association was found between the number of live births and incident CVD with the lowest risk for women with two live births. Among women in multivariable analyses, each unit increase in parity had a HR of 1.05 (CI: 1.01-1.10), and having ≥4 parity was associated with a HR of 1.86 (0.97-3.56, p-value = 0.061). Among men, in comparison with participants who had 1 child, multivariable HRs of having 2, 3, and ≥ 4 children were 1.97 (1.24-3.12), 2.08 (1.31-3.31), and 2.08 (1.30-3.34), respectively. Conclusion To the best of our knowledge, the current study is the first report on this issue in the Middle East and North Africa region, a region with a high burden of CVD. It can now be suggested that the number of parity/live birth(s) is linked to CVD among the Iranian population, with this issue being more prominent among men. Further research is needed to support our results and clarify the pathways between the number of parity/live birth(s) and CVD development among Iranian populations by considering potential risk factors, especially psycho-socio-economic risk factors.